Vaccine hesitancy among parents of adolescents and its association with vaccine uptake. Issue 14 (30th March 2015) - Roberts, James R.; Thompson, David; Rogacki, Brianna; Hale, Jessica J.; Jacobson, Robert M.; Opel, Douglas J.; Darden, Paul M.
Highlights We found a moderate degree of vaccine hesitancy in this population. The PACV, as a modified hesitancy scale, failed to predict adolescent vaccination. Two PACV items were associated with being due for HPV after a clinical visit.